2010
DOI: 10.3390/molecules15042886
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic Identification of c-Myc/Max-Regulated Genes Associated with Cytotoxicity of Artesunate towards Human Colon, Ovarian and Lung Cancer Cell Lines

Abstract: Development of novel therapy strategies is one of the major pressing topics of clinical oncology to overcome drug resistance of tumors. Artesunate (ART) is an anti-malarial drug, which also exerts profound cytotoxic activity towards cancer cells. We applied a gene-hunting approach using microarray-based transcriptome-wide mRNA expression profiling and COMPARE analyses. We identified a set of genes, whose expression was associated either with high IC50 values or low IC50 values for ART. Therefore, these genes m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 67 publications
2
24
0
Order By: Relevance
“…As expected, regulatory genes involved in signal transduction, transcription and apoptosis were prominent but, given that different gene sets associated with the compounds, remarkably similar; presumably, different genes associated with the various compounds were binned in the same category, resulting in the apparent convergence when results are displayed in this ā€œhigh-levelā€ format. Previously, a similar study to ours was performed with artesunate, but using a different cell line panel and microarray platform [85]. Interestingly, the top-ranked ā€œresistanceā€ gene in that study, SLC30A1, was also assigned by us as such (Data S1), and we found that expression of this gene was only significantly associated with ART (pā€Š=ā€Š0.0026), not the other compounds, emphasizing the unique character of each compound that we tested.…”
Section: Resultssupporting
confidence: 63%
“…As expected, regulatory genes involved in signal transduction, transcription and apoptosis were prominent but, given that different gene sets associated with the compounds, remarkably similar; presumably, different genes associated with the various compounds were binned in the same category, resulting in the apparent convergence when results are displayed in this ā€œhigh-levelā€ format. Previously, a similar study to ours was performed with artesunate, but using a different cell line panel and microarray platform [85]. Interestingly, the top-ranked ā€œresistanceā€ gene in that study, SLC30A1, was also assigned by us as such (Data S1), and we found that expression of this gene was only significantly associated with ART (pā€Š=ā€Š0.0026), not the other compounds, emphasizing the unique character of each compound that we tested.…”
Section: Resultssupporting
confidence: 63%
“…For example, it can exhibit anti-proliferative effects or induce apoptosis in various tumour cell lines in vitro and in vivo [21,22]. Additionally, Artemisia annua L. (AWL) has demonstrated significant anti-oxidant, anti-inflammatory, and anti-microbial properties [12].…”
Section: Discussionmentioning
confidence: 99%
“…These results clearly pose an interesting possibility: that the concurrent disruption of c-Myc-Max heterotetramerization might also interfere with target gene expression in other ways in various cell types [19,21]. This result could also account for the heterogeneity of primary cultures of ovarian cancer, showing small portions of stromal cells in some cases in our primary culture system, and this presence of stromal cells may affect the viability of and c-Myc function in the ovarian primary cultures.…”
Section: Discussionmentioning
confidence: 99%